Solo Song Extracurricular Management at SMA Negeri 1 Suliki Sub-District - Suciana Ramadhani; Syeilendra (Avant-garde: Jurnal Ilmiah Pendidikan Seni Pertunjukan, 2023)
This study aims to provide a description of solo song extracurricular management at SMA Negeri 1 Suliki District. This research uses a qualitative approach with a descriptive method. The researcher himself is the main instrument in this study, and is supported by stationery, cameras, and laptops as supporting instruments. Data collection techniques include literature study, observation, interviews, and documentation. The data analysis steps include data identification, data description, data clarification, data analysis, and data inference. The results showed that the management of solo song extracurricular activities consisted of planning, organizing, actuating, and controlling. (1) In planning, extracurricular activity programs include student recruitment, trainer recruitment, and preparation of training programs. The management of extracurricular activities is in accordance with the program set by the school. The source of activity funds comes from the BOS Fund, while the facilities and infrastructure used are adequate, although there are some facilities that need to be improved. (2) Organizing in the management of extracurricular activities involves the establishment of an organizational structure and formulating tasks to be carried out. (3) Actuating is carried out by motivating students so that they are enthusiastic in developing the learning process and dare to display talents and skills in singing. (4) Supervision (controlling) is carried out by the coach of solo song extracurricular activities with supervision from curriculum representatives and school principals. This supervision is carried out during the implementation of extracurricular activities. The implementation of extracurricular activities in Suliki has resulted in many achievements in the field of art, including in the solo song category.